Phase Factor Optimization for QPSK Signals Generated from MZM Based on Optical Carrier Suppression - Jianjun Yu; Long Chen (IEEE Photonics Journal)
We propose and experimentally demonstrate one novel scheme to improve the performance of the vector millimeter-wave (mm-wave) signal generated by intensity modulator based on optical carrier suppression. The phase distribution of the vector mm-wave signal after one square-law photodiode detection becomes nonuniform. We optimize the phase factor at the transmitter side and make the phase distribution of the quadrature phase-shift keying signal to be symmetrical at the receiver.